O20 Virtual reality simulation in trauma and orthopaedics; not just limited to traditional procedures alone. (3rd November 2019) - Haldar, Anil; Charalambous, Alexander; Segaren, Neil; Vaghela, Kalpesh; Montgomery, Alexander; Lee, Joshua; Akhtar, Kashif
Abstract : Introduction: Surgical training is a challenge. Over recent years there have been several well-documented factors that have reduced operating exposure. As we look to other methods of training to compensate for this, Virtual reality (VR) is increasing in popularity. Much of the previous research with VR in Orthopaedics has centred on arthroscopy and fracture fixation. Through our research, we aim to show that the benefit of VR simulation is not limited to these procedures alone but also applies to more specialist procedures. We assessed the construct validity of a VR simulator for the percutaneous insertion of a pedicle screw guidewire in the lumber spine. Methods: Twenty-four participants were recruited into this study. They consisted of medical students, postgraduate doctors and specialty doctors. They were equally divided into three groups based on previous surgical experience; novice, intermediate or expert. The simulator provided six performance metrics that were recorded for each participant. These included total score, time, fluoroscopy use, zone of wire placement, wall violation and final wire depth. Each participant performed the procedure in a set order through both left and right pedicles of lumbar vertebrae, resulting in four sets of data per person. The data was then analysed for statistical significance. Results: The results for time revealed a statistically significant difference between the three groups (p<0.001), with the novice group taking the longest time (Median 190 seconds) to complete the procedure. There was also a significant difference in fluoroscopy use between the groups, with the novice group showing the greatest use and the experienced group the lowest values at all attempts (p<0.001). Almost all participants achieved a total score of fifty, so no significant difference was seen here or with the other outcomes. Discussion and conclusion: As pedicle screw fixation is a specialised procedure, experts would most likely have had the most frequent exposure to this procedure as well as the highest exposure historically. This study therefore demonstrates the construct validity of the VR simulator for percutaneous pedicle screw fixation. VR simulation can be considered a valuable method of augmenting surgical training for more specialised procedures where exposure is already limited. This would be especially useful for trainees moving into a subspecialty field for the first time, where a procedure can be attempted with no risks to patients. The simulator can also be considered as a valid assessment tool of technical skill of a surgeon in this field.